A study on the determinants of dividend payout policy: Evidence from the ASEAN-5 countries - Artates, Princess Askha Intal (Animo Repository, 2022)
This research examined the determinants of dividend payout policy of select 139 firms from the indices of the ASEAN-5 countries namely Indonesia, Malaysia, Philippines, Thailand, and Vietnam. The study investigated the relationship between dividend payout ratio and profitability, growth opportunity, firm size, financial leverage, free cash flow, and ownership structure. The descriptive statistics provided a brief overview of the variables. A panel data regression containing 1112 observations from 2012 to 2019 was conducted. Included were various tests which led to the selection and analysis of the Random Effect model. The regression results indicated that only growth opportunity and firm size were significant determinants of dividend payout policy. It was found that growth opportunity had a positive relationship, whereas firm size had a negative effect on dividend payout policy, corroborating the agency cost theory and signaling theory. This work contributes to corporate finance literature and helps managers and investors choose stocks and formulate optimal dividend policies. The findings suggested that stakeholders should focus on organizations with higher growth potential as they are more likely to deliver dividends, and also analyze the company's total assets as high figures may signify a drop in dividend distributions.